Clinical Evaluation of the Osteoporotic Fracture Treatment Score (OF-Score): Results of the Evaluation of the Osteoporotic Fracture Classification, Treatment Score and Therapy Recommendations (EOFTT) Study - Ullrich, Bernhard W.; Schnake, Klaus John; Schenk, Philipp; Katscher, Sebastian; Bäumlein, Martin; Zimmermann, Volker; Schwarz, Falko; Schmeiser, Gregor; Scherer, Michael; Müller, Michael; Sprengel, Kai; Liepold, Katja; et al. (Global Spine Journal, 2023)
Study Design: Multicenter prospective cohort study. Objective: The study aims to validate the recently developed OF score for treatment decisions in patients with osteoporotic vertebral compression fractures (OVCF). Methods: This is a prospective multicenter cohort study (EOFTT) in 17 spine centers. All consecutive patients with OVCF were included. The decision for conservative or surgical therapy was made by the treating physician independent of the OF score recommendation. Final decisions were compared to the recommendations given by the OF score. Outcome parameters were complications, Visual Analogue Scale, Oswestry Disability Questionnaire, Timed Up & Go test, EQ-5D 5 L, and Barthel Index. Results: In total, 518 patients (75.3% female, age 75 ± 10) years were included. 344 (66%) patients received surgical treatment. 71% of patients were treated following the score recommendations. For an OF score cut-off value of 6.5, the sensitivity and specificity to predict actual treatment were 60% and 68% (AUC.684, P <.001). During hospitalization overall 76 (14.7%) complications occurred. The mean follow-up rate and time were 92% and 5 ± 3.5 months, respectively. While all patients in the study cohort improved in clinical outcome parameters, the effect size was significantly less in the patients not treated in line with the OF score’s recommendation. Eight (3%) patients needed revision surgery. Conclusions: Patients treated according to the OF score’s recommendations showed favorable short-term clinical results. Noncompliance with the score resulted in more pain and impaired functional outcome and quality of life. The OF score is a reliable and save tool to aid treatment decision in OVCF.
CRIS-Team Scopus Importer:2023-05-05
Keywords: OF classification; operative; osteoporosis; treatment; vertebral fracture

Die operative Versorgung einer bimalleolären OSG-Fraktur – Tipps und Tricks - Mayr, Jakob; Schramm, Simon; Renner, Nina; Perl, Mario; Palm, Hans Georg (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
CRIS-Team Scopus Importer:2024-05-24

Dynamic Adhesion Assay for the Functional Analysis of Anti-adhesion Therapies in Inflammatory Bowel Disease - Becker, Elisabeth; Schramm, Simon; Binder, Marie-Theres; Allner, Clarissa; Wiendl, Maximilian; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Journal of Visualized Experiments, 2018)
Gut homing of immune cells is important for the pathogenesis of inflammatory bowel diseases (IBD). Integrin-dependent cell adhesion to addressins is a crucial step in this process and therapeutic strategies interfering with adhesion have been successfully established. The anti-α4β7 integrin antibody, vedolizumab, is used for the clinical treatment of Crohn's disease (CD) and ulcerative colitis (UC) and further compounds are likely to follow. The details of the adhesion procedure and the action mechanisms of anti-integrin antibodies are still unclear in many regards due to the limited available techniques for the functional research in this field. Here, we present a dynamic adhesion assay for the functional analysis of human cell adhesion under flow conditions and the impact of anti-integrin therapies in the context of IBD. It is based on the perfusion of primary human cells through addressin-coated ultrathin glass capillaries with real-time microscopic analysis. The assay offers a variety of opportunities for refinements and modifications and holds potentials for mechanistic discoveries and translational applications.
EVALuna2:207768

Georg Schmorl prize of the German spine society (DWG) 2022: current treatment for inpatients with osteoporotic thoracolumbar fractures—results of the EOFTT study - Ullrich, Bernhard W.; Schenk, Philipp; Scheyerer, Max J.; Bäumlein, Martin; Katscher, Sebastian; Schnake, Klaus J.; Zimmermann, Volker; Schwarz, Falko; Schmeiser, Gregor; Scherer, Michael; Müller, Michael; Sprengel, Kai; et al. (European Spine Journal, 2023)
Aim: Osteoporotic thoracolumbar fractures are of increasing importance. To identify the optimal treatment strategy this multicentre prospective cohort study was performed. Purpose: Patients suffering from osteoporotic thoracolumbar fractures were included. Excluded were tumour diseases, infections and limb fractures. Age, sex, trauma mechanism, OF classification, OF-score, treatment strategy, pain condition and mobilization were analysed. Methods: A total of 518 patients’ aged 75 ± 10 (41–97) years were included in 17 centre. A total of 174 patients were treated conservatively, and 344 were treated surgically, of whom 310 (90%) received minimally invasive treatment. An increase in the OF classification was associated with an increase in both the likelihood of surgery and the surgical invasiveness. Results: Five (3%) complications occurred during conservative treatment, and 46 (13%) occurred in the surgically treated patients. 4 surgical site infections and 2 mechanical failures requested revision surgery. At discharge pain improved significantly from a visual analogue scale score of 7.7 (surgical) and 6.0 (conservative) to a score of 4 in both groups (p < 0.001). Over the course of treatment, mobility improved significantly (p = 0.001), with a significantly stronger (p = 0.007) improvement in the surgically treated patients. Conclusion: Fracture severity according to the OF classification is significantly correlated with higher surgery rates and higher invasiveness of surgery. The most commonly used surgical strategy was minimally invasive short-segmental hybrid stabilization followed by kyphoplasty/vertebroplasty. Despite the worse clinical conditions of the surgically treated patients both conservative and surgical treatment led to an improved pain situation and mobility during the inpatient stay to nearly the same level for both treatments.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Fracture; Osteoporotic; Short-segmental-stabilization; Thoracolumbar; Treatment

Innovative 3D-Bildgebung - Groh, Johannes; Schramm, Simon; Renner, Nina; Krause, J.; Perl, Markus (Die Unfallchirurgie, 2023)
Intraoperative 2D fluoroscopy is often performed for repositioning and implant control. However, this does not always provide the details needed to reliably detect joint steps or incorrect repositioning. Over the last few years, intraoperative 3D imaging has been established and further developed. Multiple studies demonstrate an advantage and better intraoperative control through 3D imaging. Examples are the upper ankle, the proximal tibia and the distal radius; the rates of intraoperative revisions with digital volume tomography (DVT) are between 20–30%. Technical advancements, such as metal artifact reductions, automated plane setting, automated screw detection, and robotic DVT devices, facilitate intraoperative operation, shorten surgical time, and provide improved image quality. By processing the data sets in the form of an immersive, computer-simulated image in terms of “augmented reality” (AR), increased precision can be achieved intraoperatively while reducing radiation exposure. The implementation of these systems is associated with costs, which are offset by cost savings from avoided revisions. Adequate counter-financing is still lacking at the present time. Intraoperative 3D imaging represents an important tool for intraoperative control. The current data situation makes it necessary to address the routine use of 3D procedures, especially in the joint area. The indications are becoming increasingly broader. Technical innovations such as robotics and AR have significantly improved 3D devices in recent years and offer high potential for integration into the OR.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Augmented reality; Digital volume tomography; Intraoperative imaging; Joints; Robotics

Intraoperative Navigation einer Distraktionsverletzung der BWS bei schwersten skoliotischen Veränderungen - Schramm, Simon; Groh, Johannes; Krause, Johannes; Perl, Mario (Die Unfallchirurgie, 2024)
The case of a 43-year-old male patient is described, who suffered several injuries due to a traffic accident, including a distraction injury to the thoracic spine. A specific feature of this case was the existing spondylodesis with material fracture and secondary loss of reduction. Due to this, the guidewires of the pedicle screws were placed in a navigation pattern in the absence of adjustable pedicles and an abnormal screw corridor. This guarantees an optimal positioning with associated patient safety.
CRIS-Team Scopus Importer:2024-05-10
Keywords: 3D imaging; Distraction injury; Multiple trauma; Navigation; Spinal trauma

Is the conservative treatment of sacral insufficiency fractures still up to date? Retrospective clinical observational study in 46 patients - Schramm, Simon; Kopschina, Carsten; Gaßmann, Karl Günter; Fujak, Albert (Orthopaedics & Traumatology-Surgery & Research, 2023)
Background: According to current forecasts, our society will grow older and older, so that the proportion of 6% of the German population from 2017 who were 80 years or older will increase further. The frequency of falls in this patient population lead to a further increase of sacral insufficiency fractures. Hypothesis: The aim of this study is to evaluate the multimodal interdisciplinary conservative therapy regime for sacral insufficiency fractures in geriatric patients, especially on the basis of mobility and the need for assistance. Patients and Methods: A cohort of patients, who were treated as inpatients at the Waldkrankenhaus St. Marien in Erlangen with ICD-10 for sacral fractures S32.1 as the main diagnosis, was retrospectively examined. Only newly diagnosed sacral insufficiency fractures were taken into account. Patients were divided into groups based on the factors hospital stay, fracture location on the sacrum, and location of concomitant pelvic ring injury. The Barthel Index, the Tinetti's Mobility Test and the Timed Up&Go Test were recorded. Results: 46 patients met the inclusion criteria. Using the conservative therapy, improvements were achieved in all patients in terms of need for care, mobility without aids and risk of falling, also patients with an anterior and posterior pelvic ring fracture. Regard a score improvement in the Barthel Index and Tinetti Mobility Test, patients with bilateral sacral insufficiency fracture (n = 17, 37.0%) did not differ significantly from patients with unilateral sacral insufficiency fracture (n = 22, 47.8%). Conclusion: In geriatric patients, decisions about therapy should always be made on an individual and interdisciplinary basis. The conservative therapy regimen continues to play an important role in this. The collected tests–consisting of Barthel Index, Tinetti Mobility Test and Timed Up&Go Test–are well suited for further reproducible, objective studies with a larger patient collective. Level of evidence: IV.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Fragility Fractures of the Pelvis; geriatric medicine; Sacral insufficiency fracture

Is the conservative treatment of sacral insufficiency fractures still up to date? Retrospective clinical observational study in 46 patients - Schramm, Simon; Kopschina, Carsten; Gaßmann, Karl-Günter; Fujak, Albert (Revue de Chirurgie Orthopedique et Traumatologique, 2023)
Background: According to current forecasts, our society will grow older and older, so that the proportion of 6 % of the German population from 2017 who were 80 years or older will increase further. The frequency of falls in this patient population lead to a further increase of sacral insufficiency fractures. Hypothesis: The aim of this study is to evaluate the multimodal interdisciplinary conservative therapy regime for sacral insufficiency fractures in geriatric patients, especially on the basis of mobility and the need for assistance. Patients and methods: A cohort of patients, who were treated as inpatients at the Waldkrankenhaus St. Marien in Erlangen with ICD-10 for sacral fractures S32.1 as the main diagnosis, was retrospectively examined. Only newly diagnosed sacral insufficiency fractures were taken into account. Patients were divided into groups based on the factors hospital stay, fracture location on the sacrum, and location of concomitant pelvic ring injury. The Barthel Index, the Tinetti's Mobility Test and the Timed Up&Go Test were recorded. Results: Forty-six patients met the inclusion criteria. Using the conservative therapy, improvements were achieved in all patients in terms of need for care, mobility without aids and risk of falling, also patients with an anterior and posterior pelvic ring fracture. Regard a score improvement in the Barthel Index and Tinetti Mobility Test, patients with bilateral sacral insufficiency fracture (n = 17, 37.0 %) did not differ significantly from patients with unilateral sacral insufficiency fracture (n = 22, 47.8 %). Conclusion: In geriatric patients, decisions about therapy should always be made on an individual and interdisciplinary basis. The conservative therapy regimen continues to play an important role in this. The collected tests – consisting of Barthel Index, Tinetti Mobility Test and Timed Up&Go Test – are well suited for further reproducible, objective studies with a larger patient collective. Level of evidence: IV.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Fragility fractures of the pelvis; Geriatric medicine; Sacral insufficiency fracture

Treatment and Outcome of Osteoporotic Thoracolumbar Vertebral Body Fractures With Deformation of Both Endplates With or Without Posterior Wall Involvement (OF 4): Short-Term Results from the Prospective EOFTT Multicenter Study - Spiegl, Ulrich J.A.; Schenk, Philipp; Schnake, Klaus John; Ullrich, Bernhard W.; Osterhoff, Georg; Scheyerer, Max J.; Schmeiser, Gregor; Bäumlein, Martin; Scherer, Michael A.; Müller, Michael; Sprengel, Kai; Liepold, Katja; et al. (Global Spine Journal, 2023)
Study Design: Multicenter prospective cohort study Objective: To analyse therapeutical strategies applied to osteoporotic thoracolumbar OF 4 injuries, to assess related complications and clinical outcome. Methods: A multicenter prospective cohort study (EOFTT) including 518 consecutive patients who were treated for an Osteoporotic vertebral compression fracture (OVCF). For the present study, only patients with OF 4 fractures were analysed. Outcome parameters were complications, Visual Analogue Scale, Oswestry Disability Questionnaire, Timed Up & Go test, EQ-5D 5L, and Barthel Index after a minimum follow-up of 6 weeks. Results: A total of 152 (29%) patients presented with OF 4 fractures with a mean age of 76 years (range 41-97). The most common treatment was short-segment posterior stabilization (51%; hybrid stabilization in 36%). Mean follow up was 208 days (±131 days), mean ODI was 30 ± 21. Dorsoventral stabilized patients were younger compared to the other groups (P <.001) and had significant better TuG compared to hybrid stabilization (P =.049). The other clinical outcomes did not differ in the therapy strategies (VAS pain: P = 1.000, ODI: P >.602, Barthel: P >.252, EQ-5D 5L index value: P >.610, VAS-EQ-5D 5L: P = 1.000). The inpatient complication rate was 8% after conservative and 16% after surgical treatment. During follow-up period 14% of conservatively treated patients and 3% of surgical treated patients experienced neurological deficits. Conclusions: Conservative therapy of OF 4 injuries seems to be viable option in patients with only moderate symptoms. Hybrid stabilization was the dominant treatment strategy leading to promising clinical short-term results. Stand-alone cement augmentation seems to be a valid alternative in selected cases.
CRIS-Team Scopus Importer:2023-05-05
Keywords: OF classification; operative; osteoporosis; spine; vertebral fracture

Treatment and Outcome of Osteoporotic Thoracolumbar Vertebral Fractures With Anterior or Posterior Tension Band Failure (OF 5): Short-Term Results From the Prospective EOFTT Multicenter Study - Osterhoff, Georg; Schenk, Philipp; Katscher, Sebastian; Schnake, Klaus John; Bäumlein, Martin; Zimmermann, Volker; Schmeiser, Gregor; Scherer, Michael A.; Müller, Michael; Sprengel, Kai; Liepold, Katja; Schramm, Simon; et al. (Global Spine Journal, 2023)
Study Design: Subgroup analysis of a multicenter prospective cohort study Objective: To analyse surgical strategies applied to osteoporotic thoracolumbar osteoporotic fracture (OF) 5 injuries with anterior or posterior tension band failure and to assess related complications and clinical outcome. Methods: A multicenter prospective cohort study (EOFTT) was conducted at 17 spine centers including 518 consecutive patients who were treated for an osteoporotic vertebral fracture (OVF). For the present study, only patients with OF 5 fractures were analysed. Outcome parameters were complications, Visual Analogue Scale (VAS), Oswestry Disability Questionnaire (ODI), Timed Up & Go test (TUG), EQ-5D 5L, and Barthel Index. Results: In total, 19 patients (78 ± 7 years, 13 female) were analysed. Operative treatment consisted of long-segment posterior instrumentation in 9 cases and short-segment posterior instrumentation in 10 cases. Pedicle screws were augmented in 68 %, augmentation of the fractured vertebra was performed in 42%, and additional anterior reconstruction was done in 21 %. Two patients (11 %) received short-segment posterior instrumentation without either anterior reconstruction or cement-augmentation of the fractured vertebra. No surgical or major complications occurred, but general postoperative complications were observed in 45%. At a follow-up of mean 20 ± 10 weeks (range, 12 to 48 weeks), patients showed significant improvements in all functional outcome parameters. Conclusions: In this analysis of patients with type OF 5 fractures, surgical stabilization was the treatment of choice and lead to significant short-term improvement in terms of functional outcome and quality of life despite a high general complication rate.
CRIS-Team Scopus Importer:2023-05-05
Keywords: OF classification; operative; osteoporosis; spine; vertebral fracture